Synthesis and Design of a Miniaturized Broadband Bandstop Filter with a Simple Structure - Chuan Shao; Rong Cai; Xinnai Zhang; Kai Xu (Micromachines)
In this paper, a miniaturized broadband bandstop filter with a simple structure is proposed, synthesized, and developed. The proposed broadband bandstop filter is designed using asymmetrically loaded parallel-coupled microstrip lines, resulting in five transmission zeros within the stopband. Closed-form formulas of the entire set of generated transmission zeros are derived to guide a practical design procedure. To demonstrate the effectiveness of the proposed concept and synthesis method, a miniaturized broadband bandstop filter centered at 3 GHz with a 20 dB rejection bandwidth of about 100% is designed, fabricated, and measured. The core circuit size of the developed broadband bandstop filter is only 0.5 λg × 0.1 λg (31.2 mm × 6.5 mm).